Metformin and Autoimmunity: A “New Deal” of an Old Drug - Ursini, Francesco; Russo, Emilio; Pellino, Gianluca; D’Angelo, Salvatore; Chiaravalloti, Agostino; De Sarro, Giovambattista; Manfredini, Roberto; De Giorgio, Roberto (Frontiers in Immunology, 2018)
Metformin (dimethyl biguanide) is a synthetic derivative of guanidine, isolated from the extracts of Galega Officinalis, a plant with a prominent antidiabetic effect. Since its discovery more than 50 years ago, metformin represents a worldwide milestone in treatment of patients with type 2 diabetes (T2D). Recent evidence in humans indicates novel pleiotropic actions of metformin which span from its consolidated role in T2D management up to a variety of regulatory properties, including cardio- and nephro-protection, as well as anti-proliferative, antifibrotic and antioxidant effects. These findings, together with ground-breaking studies demonstrating its ability to prolong healthspan and lifespan in mice, provided the basis for defining metformin as a potential anti-aging molecule. Moreover, emerging in vivo and in vitro evidence suggest that metformin can exhibit immune-modulatory features. These effects may represent a powerful contributor to anti-aging and anti-cancer properties exerted by metformin and, from another standpoint, may open the way to assess whether metformin can be a candidate molecule for clinical trials involving patients with immune-mediated diseases. In this article we will review the available preclinical and clinical evidence regarding the effect of metformin on individual cells of the immune system, with emphasis on immunological mechanisms related to the development and maintenance of autoimmunity and its potential relevance in treatment of autoimmune diseases.